Chemical Communication between Male and Female Sex of Bombyx mori - , Abhigyan Rajkhowa, Monimala Saikia, Dipankar Brahma, Nilav Ranjan Bora, Rimpi Rani Saikia, Pankaj Lushan Dutta, Indrani Nath (Archives of Current Research International, 2024)
Communication involves the systematic and symbolic exchange of information between entities. In insects, the most significant form of communication occurs between members of the same species. Silkworms primarily utilize pheromones for communication. Bombykol, the sex pheromone released by the female silk moth Bombyx mori, was first extracted by Adolf Butenandt. The biosynthesis of bombykol occurs in the pheromone gland, where various enzymes and genes participate in the biosynthesis process through an influx of extracellular Ca2+. Bombykol-sensitive ORNs are located on the antennae of male moths, which perceive the bombykol released by female moths. These ORNs are so sensitive that even a single pheromone molecule can generate an electric signal in the male moth. Once the male moth detects the bombykol molecule, the Pheromone Binding Protein plays a crucial role in enabling it to bind to the receptor without disruption. Mori, B. The substance is rapidly eliminated from its receptor site and rendered inactive by phenomenol-degrading enzymes and alcohol oxidase genes. Numerous studies and tests conducted on B. mori's sex pheromone have yielded important insights into the molecular and genetic aspects for the chemical interactions with male and female silkworms, which including the synthesis, behavioral reaction, and the perception of bombykol.